Implikasi Politik Hukum Dalam Pembentukan Uu No. 13 Tahun 2003 Terhadap Perlindungan Buruh Dalam PKWT - Muhammad Bram Glasmacher (FAIRNESS AND JUSTICE, 2020)
Basically social protection is a labor protection which aims to ensure that workers / laborers are valued for their dignity and status as human beings, not only as a factor of production (external factors, but are treated as humans with all their dignity and values (internal or constitutive factors). Law in the Formation of Law No. 13 of 2003. This research study uses a research method with a normative juridical approach with data collection techniques in the form of library research.Political Politics in Lawmaking No. 13 of 2003 is influenced by the spirit of reform to better provide protection for workers / workers after the "dark era" in the new order, and because of the problems of era labor, it has to do with the economic problems in a country, especially in Indonesia, which is a developing country, which in the process of making this law is closely linked to economic politics.clear from the implications for PKWT workers. Where this is still a pros and cons. However, this is like a double-edged knife. In terms of politics clearly this can reduce unemployment but also the number of Workers / Workers who do not understand the protection they should get. Weak understanding of the public, especially employees in private companies of labor regulations, is very likely to create injustices and legal violations that are legalized and last for a long period of time or may even last forever, even though in terms of the Manpower Act, sanctions are imposed on companies and / or individuals who violate the Law are severely punished